Critical role of the CD40–CD40-ligand pathway in regulating mucosal inflammation-driven angiogenesis in inflammatory bowel disease. Issue 9 (22nd February 2007) - Danese, S; Scaldaferri, F; Vetrano, S; Stefanelli, T; Graziani, C; Repici, A; Ricci, R; Straface, G; Sgambato, A; Malesci, A; Fiocchi, C; Rutella, S
Abstract : Background and aims: Angiogenesis is a novel component in inflammatory bowel disease (IBD) pathogenesis. We have previously shown that immune–nonimmune interactions through the CD40–CD40-ligand (CD40L) pathway might sustain gut inflammation, although their effect on regulating inflammation-driven angiogenesis is unknown. The present study evaluated the role of the CD40–CD40L interaction in the promotion of immune-mediated angiogenesis in IBD. Methods: Human nonimmune cells of colonic origin—namely, human intestinal fibroblasts (HIFs) and human intestinal microvascular endothelial cells (HIMECs)—were activated with either soluble CD40L (sCD40L), or CD40 + D1.1 cells or CD40L-activated lamina propria T (LPT) cells before measuring pro-angiogenic cytokine release. Blocking antibodies to either CD40 or CD40L were used to disrupt the CD40–CD40L interaction. The dextran sodium sulphate (DSS) model of experimental colitis in CD40 and CD40L knockout mice was established to assess whether the CD40–CD40L pathway was implicated in controlling inflammation-driven angiogenesis in vivo . Results: Engagement of CD40 on HIFs promoted the release of vascular endothelial growth factor (VEGF), interleukin-8 (IL-8) and hepatocyte growth factor (HGF). LPT cells were potent inducers of pro-angiogenic cytokine secretion by HIFs. Supernatants from sCD40L-activated HIFs induced migration of HIMECs and tubule formation, both of which were inhibited by blocking antibodies to either VEGF, IL-8 or HGF. Both CD40- and CD40L-deficient mice were protected from DSS-induced colitis and displayed a significant impairment of gut inflammation-driven angiogenesis, as assessed by microvascular density. Conclusions: The CD40–CD40L pathway appears to be crucially involved in regulating inflammation-driven angiogenesis, suggesting that strategies aimed at blocking CD40–CD40L interactions might be beneficial in acute and chronic intestinal injury.